2008
DOI: 10.1080/13803390701380591
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of depressive symptoms on prospective and retrospective memory in old age

Abstract: The effects of depressive symptoms on prospective and retrospective memory were examined in a population-based sample of elderly persons (n = 404). Depression was assessed using the Comprehensive Psychopathological Rating Scale and treated as a continuous variable. The variation in depressive symptoms ranged from no symptoms to presence of a clinical depression. Depressive symptoms had a negative effect on consolidation and retrieval in retrospective memory. However, the retrospective, but not the prospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
2
5
1
Order By: Relevance
“…The findings relating to depression are consistent with previous research showing that depression tends not to be associated with event based PM impairments (Livner, Berger, Jones & Backman, 2005;Kliegel & Jager, 2006). Furthermore, the significant correlations found within the alcohol dependent group between event based PM task performance and the two alcohol use variables (with over 50% of the variance in regular task performance being shared with units of alcohol consumed per week), highlight the likely primacy of neurological changes associated with alcohol dependence, rather than the effects of co-morbid psychopathology, in influencing PM performance amongst alcohol dependents.…”
Section: Alcohol Dependence and Pm Performancesupporting
confidence: 82%
“…The findings relating to depression are consistent with previous research showing that depression tends not to be associated with event based PM impairments (Livner, Berger, Jones & Backman, 2005;Kliegel & Jager, 2006). Furthermore, the significant correlations found within the alcohol dependent group between event based PM task performance and the two alcohol use variables (with over 50% of the variance in regular task performance being shared with units of alcohol consumed per week), highlight the likely primacy of neurological changes associated with alcohol dependence, rather than the effects of co-morbid psychopathology, in influencing PM performance amongst alcohol dependents.…”
Section: Alcohol Dependence and Pm Performancesupporting
confidence: 82%
“…Livner et al (2008) found a negative relationship between depressive symptoms and both free and cued recall. Harris and Menzies (1999) found no relationship of nonclinical depression with recall.…”
Section: Depression and Retrospective Memorymentioning
confidence: 98%
“…Impairments in cognitive resources should particularly affect performance in resource-demanding self-initiated processes that are often required to perform PM tasks. Livner, Berger, Karlsson, and Bäckman (2008) examined a sample of older nonclinically depressed adults with a naturalistic PM task. Participants had to remind the experimenter to do something at the end of the experiment.…”
Section: Depression and Event-based Pm Performancementioning
confidence: 99%
“…Results concerning internal strategy were more contrasted, revealing that an increase in depressive symptoms or routinization is associated with more internal strategy use uniquely for older participants. Memory strategies are a way to compensate memory performance (Bä ckman and Dixon, 1992) and an increase in external and internal strategy use could signify the attempt to cope with memory reduction occurring with aging (Zacks et al, 2000) or depressive symptoms (Livner et al, 2008). Moreover, increased routinization could compensate the reduction of resources with aging (Bouisson, 2002), and increased strategy use could be due to the attempt to compensate memory decline.…”
Section: Discussionmentioning
confidence: 99%
“…However, this negative effect was more pronounced in free recall than in recognition, so depression could principally affect effortful processes in memory. Furthermore, depression could affect consolidation and recovery of information in memory (Livner et al, 2008). It might also affect the use of memory strategies, which are generally effortful as in the use of mental imagery (Hart et al, 1987;Kindermann and Brown, 1997).…”
Section: Introductionmentioning
confidence: 99%